Depletion of CD169+ border-associated macrophages induces Parkinson’s disease-like behavior - Ohki, Takuto; Kitamura, Kai; Tokutake, Katsuhiro; Saeki, Sota; Yamamoto, Michiro; Takasu, Masaki; Hirata, Hitoshi (Frontiers in Neuroscience, 2025)
Parkinson’s disease (PD) and Alzheimer’s disease (AD) present with complex behavioral symptoms that can arise in the absence of overt structural brain damage. Recent evidence suggests that border-associated macrophages (BAMs) located at the brain’s interfaces regulate central nervous system function, yet the specific roles of distinct BAM subsets remain largely undefined. By reanalyzing single-nucleus RNA sequencing data from postmortem PD brains, we identified a BAM subset expressing CD169 that was significantly reduced in patients compared with controls. To examine their function, we employed CD169-DTR mice to selectively ablate CD169+ BAMs and evaluated behavioral and histological changes. Depletion of CD169+ BAMs induced tremors, abnormal hindlimb reflexes, and heightened anxiety-like behavior without dopaminergic neuron loss. Histological analysis revealed a pronounced reduction of mitral and tufted cells in the olfactory bulb, indicating disruption of olfactory-limbic circuitry. These findings demonstrate that CD169+ BAMs are critical for maintaining neural network stability and motor function, and that their loss can elicit PD-like phenotypes in the absence of classical dopaminergic neurodegeneration. This work establishes a novel mouse model linking brain-border immune cell dysfunction to Parkinsonian pathology and highlights a neuroimmune mechanism that may contribute to the onset of PD-like disorders.